Frights, camera, action! : the junior novel - Finn, Perdita (New York : Little, Brown and Co., 2014)
"When Draculaura is led to believe she's the rightful heir to the vampire throne, she and her best ghoulfriends are whisked away to Transylvania for a royal coronation to die for. But they soon discover the hunt for the queen is not over yet. The Ghouls must locate an ancient artifact known as the Vampire's Heart in order to discover the identity of the true Vampire Queen"--Back cover.
"Based on the screenplay written by Audu Paden & Dan Serafin"--T.p.
"Based on the movie"--Front cover.
5.0
3-6
3-6
Keywords: High schools -- Juvenile fiction; Monsters -- Juvenile fiction; Queens -- Juvenile fiction; Friendship -- Juvenile fiction; High schools -- Fiction; Schools -- Fiction; Monsters -- Fiction; Kings, queens, rulers, etc. -- Fiction; Friendship -- Fiction; Fantasy; High schools -- Fiction; School stories; Monsters -- Fiction; Queens -- Fiction; Friendship -- Fiction; Movie novels; Fantasy fiction; Science fiction